2021
DOI: 10.1016/j.xphs.2020.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of 17-α-Ethinyl-Estradiol and 17-β-Estradiol on Transport Via the Intestinal Proton-Coupled Amino Acid Transporter (PAT1) Investigated In Vitro and In Vivo

Abstract: The proton-coupled amino acid transporter, PAT1, is known to be responsible for intestinal absorption drug substances such as gaboxadol and vigabatrin. The aim of the present study was to investigate, if 17a-ethinyl-estradiol (E-E2) and 17-b-estradiol (E) inhibit PAT1-mediated intestinal absorption of proline and taurine in vitro in Caco-2 cells and in vivo using Sprague-Dawley rats to assess the potential for taurine-drug interactions. E and E-E2 inhibited the PAT1-mediated uptake of proline and taurine in Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
0
7
0
1
Order By: Relevance
“…Likewise, 17-α-ethinyl-estradiol is a non-translocating and non-competitive inhibitor of proton-coupled amino acids (Nielsen et al, 2021) being capable of inducing alterations in the endocrine system in living organisms at concentrations in the water below 1 ng L -1 (Hansen et al, 1998;Purdom et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, 17-α-ethinyl-estradiol is a non-translocating and non-competitive inhibitor of proton-coupled amino acids (Nielsen et al, 2021) being capable of inducing alterations in the endocrine system in living organisms at concentrations in the water below 1 ng L -1 (Hansen et al, 1998;Purdom et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Shan et al suggested that estradiol binds to PAT1 and thereby changes the conformation of the PAT1 protein from an open to a closed state, thereby decreasing transport activity [ 267 ]. Recently, Nielsen et al revisited this to assess the potential for drug-drug interactions, showing that 17-α-ethinyl-estradiol (E-E2, Figure 6 ) inhibited PAT1-mediated Pro and taurine transport in vitro in Caco-2 cells [ 268 ]. Under slightly acidic extracellular conditions, E2 and E-E2 inhibited Pro uptake with IC 50 -values of 10.0 ± 3.2 µM and 50.0 ± 14.3 µM, respectively [ 268 ].…”
Section: Proton-coupled Amino Acid Transporter 1 (Pat1)mentioning
confidence: 99%
“…Recently, Nielsen et al revisited this to assess the potential for drug-drug interactions, showing that 17-α-ethinyl-estradiol (E-E2, Figure 6 ) inhibited PAT1-mediated Pro and taurine transport in vitro in Caco-2 cells [ 268 ]. Under slightly acidic extracellular conditions, E2 and E-E2 inhibited Pro uptake with IC 50 -values of 10.0 ± 3.2 µM and 50.0 ± 14.3 µM, respectively [ 268 ]. The uptake of taurine was inhibited by E and E-E2 with IC 50 -values of 8.7 ± 5.1 µM and 22.9 ± 15.5 µM, respectively [ 268 ].…”
Section: Proton-coupled Amino Acid Transporter 1 (Pat1)mentioning
confidence: 99%
See 1 more Smart Citation
“…O ATB 0,+ apresenta maior afinidade para aminoácidos como a leucina e lisina do que para a β-alanina Ganapathy et al, 2008) (Fei et al, 1994). Eles também cumprem papel importante no transporte de substâncias medicamentosas, facilitando dessa forma a absorção via oral de alguns medicamentos (Nielsen et al, 2021).…”
Section: Fontes Alimentares De β-Alaninaunclassified